2010
DOI: 10.1128/jvi.01216-10
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Virus Replication Induces Cell Cycle Arrest in G 0 /G 1 Phase

Abstract: Many viruses interact with the host cell division cycle to favor their own growth. In this study, we examined the ability of influenza A virus to manipulate cell cycle progression. Our results show that influenza A virus A/WSN/33 (H1N1) replication results in G0/G1-phase accumulation of infected cells and that this accumulation is caused by the prevention of cell cycle entry from G0/G1 phase into S phase. Consistent with the G0/G1-phase accumulation, the amount of hyperphosphorylated retinoblastoma protein, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
127
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(141 citation statements)
references
References 62 publications
11
127
1
Order By: Relevance
“…Our previous studies of nonhuman primates and mice infected with highly pathogenic viruses have also shown the differential regulation of cell cycle-related genes (3,4), suggesting that this is an important mechanism for host survival during lethal influenza virus infection. This is interesting, because it has been shown that influenza virus infection induces cell cycle arrest, which promotes a favorable environment for influenza virus protein expression (10). Consequently, the activation of cell cycle regulatory genes counters this mechanism by promoting host cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies of nonhuman primates and mice infected with highly pathogenic viruses have also shown the differential regulation of cell cycle-related genes (3,4), suggesting that this is an important mechanism for host survival during lethal influenza virus infection. This is interesting, because it has been shown that influenza virus infection induces cell cycle arrest, which promotes a favorable environment for influenza virus protein expression (10). Consequently, the activation of cell cycle regulatory genes counters this mechanism by promoting host cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Targets of miR-449a/b include Cdk6 and Cdc25a, while the miR-34 family functions as tumor suppressors by targeting antiapoptotic mRNAs, including Ccne2, Bcl-2, and Cdk6 (21,39,63). Regulation of these mRNAs by the miR-449 and miR-34 families causes cell cycle arrest at G 0 /G 1 and the induction of apoptosis, both of which have been shown to be important to the infA life cycle (19,40,42). Furthermore, profiles of leukocytes from infected patients showed that profound changes in cell cycle regulation were associated with an increase in the severity of disease caused by infA infection (49).…”
Section: Figmentioning
confidence: 99%
“…Several factors, such as the cyclin/cyclin-dependent kinase (cyclin/CDK) complex, closely regulate all the processes of each phase (15). If cell proliferation is disturbed by infection with the influenza A virus, the host cells are arrested in the G0̸G1 phase (16) and if the DNA damage is not repaired, the cells enter the apoptotic process (17).…”
Section: Discussionmentioning
confidence: 99%